Rheological properties and 3D-printability of cellulose nanocrystals/deep eutectic solvent electroactive ion gels. (15th August 2022) - Vorobiov, Vitaly K.; Sokolova, Maria P.; Bobrova, Natalya V.; Elokhovsky, Vladimir Yu.; Smirnov, Michael A.
Abstract: 3D-printing of stimuli-responsible electroactive gels containing biopolymers, such as cellulose nanocrystals (CNC), is a prospective area of material science. Deep eutectic solvents (DES) have shown a potential interest for applications in electroactive materials as well as for processing of cellulose. In this work, CNC obtained by two methods of processing microcrystalline cellulose were used for preparation of inks containing 6–15 wt% of CNC in polymerizable DES based on choline chloride/acrylic acid. The impact of rheological properties of the inks on 3D-printability was evaluated. The effect of CNC content on the morphology and ionic conductivity of 3D-printed electroactive composite gels was investigated using atomic force microscopy and impedance spectroscopy measurements. The potential application of the obtained materials for designing of a 3D-printed tactile sensor have been demonstrated. Graphical abstract: Unlabelled Image